A comparative analysis of the dynamics of carbohydrate metabolism in ski-racers during training with alternating middle altitude hypoxia/normoxia and normoxia - Bakhareva, A.; Isaev, A.; Aminov, A.; Reiter, A. (Advances in Health Sciences Research, 2019)
The purpose of the article is to analyze the dynamics of indicators of carbohydrate metabolism at rest in ski-racers with different training programs. Materials and methods: 17 male ski-racers aged 18-23 years participated in the study. The first group (1) consisted of cross-country skiers with training under conditions of alternating middle altitude hypoxia (May-August-October) and normoxia (n = 7); the second group - cross-country skiers with training under conditions of normoxia (n = 10). The study was conducted in the preparatory (July) and competition period (December). Indicators of carbohydrate metabolism (glycogen level, glucose concentration, lactic acid concentration and blood acid status (pH)) were obtained with a non-invasive AMP blood analyzer (Ukraine). Results: it was established that by the competition period in the 1st group of ski-racers there was a decrease in glucose concentration by 6.66% (p> 0.05) and lactic acid by 10.00% (p> 0.05); in athletes of the 2nd group an increase in lactic acid by 12.50% (p <0.05) and glucose by 7.40% (p> 0.05) was recorded. Conclusion: the combined regime of middle altitude hypoxia and normoxia allowed increasing aerobic energy supply by the competition period. The trend of a decrease in the concentration of glucose and lactic acid in athletes of the 1st group in the competition period indicated a decrease in insulin secretion and an increase in the activity of lipolysis enzymes